What should a website dedicated to the postnatal period contain? A Delphi survey among parents and professionals. (October 2017) - Slomian, J.; Emonts, P.; Erpicum, M.; Vigneron, L.; Reginster, J.Y.; Bruyère, O.
Abstract: Objectives: Mothers have a great need for information during the postnatal period. Trying to meet this need, mothers are increasingly turning to the Internet. Nevertheless, many women have stated that they often or always found that the information that they found on the Internet was incomplete or wrong. Many women therefore believe that health professionals should suggest reliable Internet websites for new mothers. The aim of this study was therefore to find a consensus on the content of a reliable and centralized website dedicated to mothers from the end of pregnancy to 1 year after childbirth. Design: Two rounds of an online Delphi survey were used in this study. Setting and participants: The panel of participants involved in the survey included parents (both mothers and fathers) and professionals (health professionals and professionals of early childhood for mothers of children aged 0 to 2 years). Findings: Ninety-six parents and professionals participated in the first round (37.7 ± 9.76 years; 84.4% of women) and 78 in the second round. The majority of participants (94.6%) thought that a centralized website could help mothers from pregnancy to one year after childbirth. The content that the experts would like to find on a website were themed into five categories: "infants' information", "parents' information", "administrative information", "professionals' information" and "type of resources". In each category, experts highlighted the key words that they found important and should be reported on the website. The most important items highlighted by participants were baby's feeding/breastfeeding (92.8%), babies' needs (84.1%), baby blues (77.9%), postpartum depression (72.1%), management of the couple's relationship (72.1%), women's right to postnatal care (83.6%), links to reliable documents (63.9%) and a list of useful contacts (52.5%). Conclusions: This study helped to understand the questions that mothers ask themselves during the postpartum period and provided priorities to respond to their questions in the process of developing a website. Highlights: New mothers have a lot of questions during the postnatal period. Many mothers seek answers to these questions on the Internet. This study sought to establish topics women would be most interested in reading online. Mothers would like accurate information relating to both infant and parent needs. They also want administrative information such as availability of particular services.